MENINGKATKAN PEMAHAMAN SURAH AD-DHUHA MELALUI PROBLEM BASED LEARNING (PBL) PADA SISWA KELAS VI SD N 053985 SUKA DAMAI - Rita Diani (CV. Arsy Persada Quality, 2024)
This study aims to improve the understanding of Grade VI students at SDN 053985 Suka Damai regarding Surah Ad-Dhuha through the application of the Project-Based Learning (PBL) model. The study utilized Classroom Action Research (CAR) conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The results indicated a significant improvement in students’ comprehension of the meaning of Surah Ad-Dhuha, as well as their ability to apply the values contained in the surah in their daily lives. This improvement was evidenced by the comparison of pre-cycle, Cycle I, and Cycle II results.